Roof solar collector and vertical stack for enhancing indoor ventilation of single-storey shophouse in Malaysia - Mohammad Yusoff, Wardah Fatimah (2012)
The climatic conditions in Malaysia which result in small air temperature differences between the indoor and outdoor of naturally ventilated buildings have reduced the efficiency of stack ventilation. A viable alternative in enhancing stack ventilation is the utilization of a solar induced ventilation. In this thesis, a solar induced ventilation that utilizes a roof solar collector and a vertical stack is proposed for the application in small and medium enterprise (SME) premises. The aim is to enhance the air flow rate in the indoor working area. The research methodologies employed were experiment and simulation modelling. A prototype of the proposed strategy was constructed in the experiment to examine its ability in inducing stack ventilation in a hot and humid climate. Its potential performance was further evaluated using simulation modelling. The investigations involved the orientation of the solar collector and the height of the vertical stack. Simulation modelling was also employed to investigate the application of the prototype in the selected typology of SME building, which is a single storey shophouse. Results were analyzed and presented in terms of five variables, namely temperature, air velocity, mass flow rate, air flow rate and air exchange rate. The findings from the experiment show that the prototype is able to induce stack ventilation in a hot and humid climate. High air temperature difference between the stack air and the ambient air was attained by the prototype, which was 9.9 ºC, for 877 W/m² solar irradiance. The result of orientation study indicated that the recommended orientation throughout the year is west-facing. Meanwhile, the investigations of vertical stack height indicated that the higher the stack is, the lower the air temperature inside the stack, but the greater the induced mass flow rate. The application of the prototype in the selected building also demonstrated positive results, in which it was able to enhance the indoor air flow rate and air exchange rate,as well as reduce the indoor air temperature. The prototype with 1 m width solar collector and 4 m high vertical stack was able to reduce the indoor air temperature by an average 0.6 ºC, increase the indoor air flow rate of less than 0.1 m³/s and provide the air exchange rate around 5 to 16 ACH. The air temperature reduction, air flow rate increment and air exchange rate were greater with the enhancement of solar collector width. The recommended width of the solar collector for the application in the selected building is 3 m. The prototype with 3 m width solar collector and 4 m high vertical stack was able to provide the highest indoor air temperature reduction of 2.6 ºC (for 446 W/m² solar irradiance), the highest indoor air flow rate increment of 0.24 m³/s (for 750 and 839 W/m² solar irradiance) and the highest air exchange rate of 26 ACH (for 839 W/m² solar irradiance). In summary, the research shows potential application of the proposed strategy in enhancing the indoor ventilation of a single storey shophouse in Malaysia.